The discrete simulation of aggregation and sedimentation of micro- and nanoparticles in suspensions - Баранець, Віталія Олександрівна; Кизилова, Наталья Николаевна (Bulletin of V.N. Karazin Kharkiv National University, series «Mathematical modeling. Information technology. Automated control systems», 2019)
The aggregation of particles in technical nanofluids is investigated as a mechanism of their aging. It have been established that nanofluid viscosity increases, and thermal conductivity decreases due to aggregation. The region of particle-free fluid is formed during the sedimentation in the upper part of the tube (zone I). Zone IIa, filled with sedimenting single particles and aggregates of a small number of particles is located next. Zone IIb filled with the large aggregates is followed. Next zone IIc consists of the large aggregates that form a porous framework. Bottom layer III consists of the compactly placed aggregates without a fluid. Dynamic curves H(t) obtained from the experiments make it possible to evaluate the developed theoretical models. A review of the known experimental data on the aggregation and sedimentation of various types of nanoparticles is presented and the available theoretical models that have shown significant differences between the theoretical and experimental sedimentation curves are reviewed. The discrete particle dynamics method which allows performing computer simulations with any geometry and location of the tube is used for numerical calculations. The results of calculations using theoretical and experimental data shows that the sedimentation is faster in the presence of sliding on the particle’s surfaces which is more evident in inclined tubes. With an increase in the inclination angle of the tube the sedimentation rate increases at  , and at large angles it decreases  immediately after the start of sedimentation. Thus the evaluation of nanofluid aging may be accelerated if the test is conducted in an inclined tube. A quantitative indicator of aging based on the nanoparticle sedimentation rate in a tube is proposed. A modification of the particle dynamics method which accounts for the second-order slide condition at the fluid-solid interface is proposed. Computer simulations of the sedimentation in straight and inclined tubes have been carried out. A correspondence of theory and experiment has been shown.